The Legal Representation of Parents and Children During Placement Procedures in the Light of Article 8 ECHR - Iris Reinders; Joost Huijer (Utrecht Law Review)
The justification of the out-of-home placement and therefore the separation of a parent and a child is assessed by the European Court of Human Rights (ECtHR) against both substantive (is the infringement provided for by law, does it serve to protect one of the interests as listed in paragraph 2 Article 8 ECHR and is it necessary in a democratic society), and procedural obligations (do have parents and children been given the opportunity to effectively participate in the decision-making process that led to the out-of-home placement) which derive from Article 8 ECHR. The distinction between substantive and procedural obligations is not always easy to make: they can overlap and influence each other. It is, however, important in each case to make sure which obligations are violated because this determines the nature of the failure of the state. This distinction will be made in this article in relation to the legal position of parents and children according to the ECtHR in procedures about the out-of-home placement of the child.